Recent Advances in Potential Clinical Application of Ghrelin in Obesity - Christine Delporte (Hindawi Limited, 2012)
Ghrelin is the natural ligand of the growth hormone secretagogue receptor (GHS-R1a). Ghrelin is a 28 amino acid peptide possessing a unique acylation on the serine in position 3 catalyzed by ghrelin O-acyltransferase (GOAT). Ghrelin stimulates growth hormone secretion, but also appetite, food intake, weight gain, and gastric emptying. Ghrelin is involved in weight regulation, obesity, type 2 diabetes, and metabolic syndrome. Furthermore, a better understanding of ghrelin biology led to the identification of molecular targets modulating ghrelin levels and/or its biological effects: GOAT, ghrelin, and GHS-R1a. Furthermore, a recent discovery, showing the involvement of bitter taste receptor T2R in ghrelin secretion and/or synthesis and food intake, suggested that T2R could represent an additional interesting molecular target. Several classes of ghrelin-related pharmacological tools for the treatment of obesity have been or could be developed to modulate the identified molecular targets.